A Short Performance Anxiety Scale for Musicians - Mazzarolo, Isabella; Schubert, Emery (Frontiers in Psychology, 2022)
Given the prevalence of debilitating anxiety associated with music performance, there is a need for rapid, pinpointed assessment of the extent to which an individual experiences music performance anxiety (MPA). A short, five item scale, the Mazzarolo Music Performance Anxiety Scale (M-MPAS), was developed to capture retrospective self-reported estimates of the frequency, intensity and aversion tendency associated with performing music. 102 musicians completed the scale, as well as an established MPA inventory. The M-MPAS was found to be internally reliable (Cronbach’s alpha = .894) with all items being statistically relevant to the overall scale. Furthermore, the M-MPAS was correlated with the relevant factors of the established MPA measure (r = .791), suggesting that the new scale exhibited good construct validity. M-MPAS is easy to score, with a scale range of 0 to 30. A score of 11 or above is suggested as the range in which a diagnosis of potential high MPA can be made, but more research into this and the psychometric robustness of the scale is called for. Nevertheless, the reliability and validity demonstrated in the present study, along with the brevity of the M-MPAS suggest that the newly proposed scale may offer considerable triaging benefits for pinpointed assessment of the extent to which an individual experiences MPA.